Buya Hamka's Views on Gathering in Al-Azhar Tafsir and Its Relevance to the Alek Bakajang Tradition - Gusti Rafel; Jani Arni; Saifullah Saifullah (International Journal of Research, 2024)
Silaturrahmi is a command from Allah as stated in the Qur’an. Buya Hamka, in his Tafsir Al-Azhar, explains that silaturrahmi means fostering bonds of compassion among all human beings, as humanity fundamentally originates from a single soul. This concept of silaturrahmi is also implemented by Indonesian society through various traditions, such as the Alek Bakajang tradition. Alek Bakajang is a longstanding tradition passed down through generations to strengthen relationships among all elements of society in Nagari Gunuang Malintang, Pangkalan Koto Baru Subdistrict, Lima Puluh Kota Regency, West Sumatra. In modern times, this tradition is often associated with "open house" gatherings and “halal bi halal”, commonly held after the celebration of Eid al-Fitr. This study aims to analyze Hamka's perspective on silaturrahmi and its relevance to the Alek Bakajang tradition. It combines library research with field research and employs a qualitative approach. Data were collected from Hamka’s Tafsir Al-Azhar as well as through observation and interviews with informants in the study area. The findings reveal that Hamka’s view on silaturrahmi aligns closely with the values embedded in the Alek Bakajang tradition. In the context of silaturrahmi, the Alek Bakajang tradition carries profound meanings, including understanding and preserving family lineage, always remembering Allah and supporting relatives, forgiving one another within the community, and promoting good counsel and mutual advice.